Optical coherence tomography : a clinical and technical update - Cunha-Vaz, José; Bernardes, Rui (Biological and Medical Physics, Biomedical Engineering, 2012)
Optical Coherence Tomography represents the ultimate noninvasive  ocular imaging technique although being in the field for over two-decades. This book encompasses both medical and technical developments and recent achievements. Here, the authors cover the field of application from the anterior to the posterior ocular segments (Part I) and present a comprehensive review on the development of OCT. Important developments towards  clinical applications are covered in Part II, ranging from the adaptive optics to the integration on a slit-lamp, and passing through new structural  and functional information extraction from OCT data. The book is intended to be informative, coherent and comprehensive for both the medical and technical communities and aims at easing the communication between the two fields and bridging the gap between the two scientific communities.